The dual role of state shareholders in disclosed corporate misconduct: Evidence from China. (22nd November 2022) - Hu, Chenhao
Abstract: By adopting a legitimacy perspective rooted in institutional theory, this study investigates the dual role of state ownership in corporate misconduct in emerging economies: monitoring role constraining misconduct commission and patronage role leading to less disclosure. Using a sample of listed firms in China, we find a negative relationship between state ownership and corporate misconduct. Furthermore, the negative effect of state ownership on misconduct will be stronger when the firm affiliation is high and the firm has politically connected executives. The impact will be weaker when the number of local listed firms is greater and the regional inspection is intense.